2019
DOI: 10.1002/nau.24238
|View full text |Cite
|
Sign up to set email alerts
|

NNT‐AS1 enhances bladder cancer cell growth by targeting miR‐1301‐3p/PODXL axis and activating Wnt pathway

Abstract: As a tumor involved in the urinary system, bladder cancer (BC) seriously threatens human health. Emerging as crucial biomarkers, long noncoding RNAs (lncRNAs) play an important role in the regulation of many cancers. lncRNA NNT-AS1 has been studied in a series of cancers, whereas its role and potential molecular mechanism was poorly understood in BC. Here, we found that NNT-AS1 was upregulated in BC cells. Functionally, the silencing of NNT-AS1 inhibited cell proliferation, migration, invasion, and endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Current research shows that NNT-AS1 is highly expressed in most tumors, including non-small-cell lung cancer (NSCLC) [ 16 , 17 , 18 , 19 ], lung squamous cell carcinoma (LUSC) [ 20 ], colorectal cancer (CRC) [ 14 ], hepatocellular carcinoma (HCC) [ 21 ], cholangiocarcinoma (CAA) [ 22 , 23 , 24 ], cervical cancer [ 25 , 26 ], osteosarcoma [ 27 , 28 ], bladder cancer [ 29 , 30 ], and glioma [ 31 ]. These results have been verified in the corresponding tumor tissues or tumor cells.…”
Section: The Aberrant Expression Of Nnt-as1 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Current research shows that NNT-AS1 is highly expressed in most tumors, including non-small-cell lung cancer (NSCLC) [ 16 , 17 , 18 , 19 ], lung squamous cell carcinoma (LUSC) [ 20 ], colorectal cancer (CRC) [ 14 ], hepatocellular carcinoma (HCC) [ 21 ], cholangiocarcinoma (CAA) [ 22 , 23 , 24 ], cervical cancer [ 25 , 26 ], osteosarcoma [ 27 , 28 ], bladder cancer [ 29 , 30 ], and glioma [ 31 ]. These results have been verified in the corresponding tumor tissues or tumor cells.…”
Section: The Aberrant Expression Of Nnt-as1 In Cancermentioning
confidence: 99%
“…Among them, the Wnt/β–catenin pathway mainly regulates the fate of cells during development [ 48 ]. As shown in Figure 2 A, a study found that in bladder cancer, NNT-AS1 can up-regulate podocalyxin-like (PODXL) by sponging miR-1301-3p, which in turn activates the Wnt pathway-related proteins, including CDK1, cyclin D1, MYC, AXIN2, and CTNNB1 (β-catenin) [ 29 ]. In CAA, the up-regulated NNT-AS1 can compete with miR-485 to bind to B-cell CLL/lymphoma 9 protein (BCL9), thereby increasing the expression of BCL9 and promoting the proliferation, migration, and invasion of CCA cells [ 22 ].…”
Section: Nnt-as1 Regulates Tumor Progression By Sponging Mirnasmentioning
confidence: 99%
“…For example, miR-1301-3p inhibited Wnt/β-catenin signaling pathway through targeting BCL9 in hepatocellular carcinoma [12] . Similarly, NNT-AS1 promoted bladder cancer cell proliferation by targeting miR-1301-3p/PODXL axis and activating Wnt pathway [13] . Besides, ABHD11-AS1 and LINC01433 upregulated STAT3 level by sponging miR-1301-3p and promoted tumor progression in papillary thyroid carcinoma and hepatocellular carcinoma, respectively [14,15] .…”
Section: Discussionmentioning
confidence: 97%
“…With the advancement of RNA-Seq technologies, lncRNAs are closely associated with bladder cancer (21). Previous studies have revealed that LINC00858, a novel lncRNA, was upregulated in several cancers and functioned as a tumor promoter in colorectal cancer, non-small cell lung cancer and osteosarcoma (8,15,(22)(23)(24). LINC00858 promoted cell proliferation, migration and invasion by acting as a ceRNA of microRNA in the aforementioned cancers.…”
Section: Discussionmentioning
confidence: 99%